In Vitro Evaluation of the Impact of the Probiotic E. coli Nissle 1917 on Campylobacter jejuni’s Invasion and Intracellular Survival in Human Colonic Cells - Helmy, Yosra A.; Kassem, Issmat I.; Kumar, Anand; Rajashekara, Gireesh (Frontiers in Microbiology, 2017)
Campylobacter jejuni is a leading cause of bacterial food poisoning in humans. Due to the rise in antibiotic-resistant Campylobacter, there exists a need to develop antibiotic-independent interventions to control infections in humans. Here, we evaluated the impact of E. coli Nissle 1917 (EcN), a probiotic strain, on C. jejuni’s invasion and intracellular survival in polarized human colonic cells (HT-29). To further understand how EcN mediates its impact, the expression of 84 genes associated with tight junctions and cell adhesion was profiled in HT-29 cells after treatment with EcN and challenge with C. jejuni. The pre-treatment of polarized HT-29 cells with EcN for 4 h showed a significant effect on C. jejuni’s invasion ( 2 log reduction) of the colonic cells. Furthermore, no intracellular C. jejuni were recovered from EcN pre-treated HT-29 cells 24 h post-infection. Other probiotic strains tested had no significant impact on C. jejuni invasion and intracellular survival. C. jejuni decreased the expression of genes associated with epithelial cells permeability and barrier function in untreated HT-29 cells. However, EcN positively affected the expression of genes that are involved in enhanced intestinal barrier function, decreased cell permeability, and increased tight junction integrity. The results suggest that EcN impedes C. jejuni invasion and subsequent intracellular survival by affecting HT-29 cells barrier function and tight junction integrity. We conclude that EcN might be a viable alternative for controlling C. jejuni infections.